A Singlet Oxygen Generating Agent by Chirality‐dependent Plasmonic Shell‐Satellite Nanoassembly. Issue 18 (23rd February 2017) - Gao, Fengli; Sun, Maozhong; Ma, Wei; Wu, Xiaoling; Liu, Liqiang; Kuang, Hua; Xu, Chuanlai
Abstract : Photodynamic therapy (PDT) agent, which generates singlet oxygen ( 1 O2 ) under light, has attracted significant attention for its broad biological and medical applications. Here, DNA‐driven shell–satellite (SS) gold assemblies as chiral photosensitizers are first fabricated. The chiral plasmonic nanostructure, coupling with cysteine enantiomers on its surface, exhibits intense chiroplasmonic activities (−40.2 ± 2.6 mdeg) in the visible region. These chiral SS nanoassemblies have high reactive oxygen species generating efficiency under circular polarized light illumination, resulting in a 1 O2 quantum yield of 1.09. Meanwhile, it is found that SS could be utilized as PDT agent with remarkable efficiency under right circular polarized light irradiation in vitro and in vivo, allowing X‐ray computed tomography (CT) and photoacoustics (PA) imaging for tumors simultaneously. The achievements reveal that the enantiomer‐dependent and structure‐induced nanoassemblies play an important role in PDT effects. The present researches open up a new avenue for cancer diagnose and therapy using chiral nanostructures as multifunctional platform. Abstract : Label‐free chiral photodynamic therapy (PDT) agents have been fabricated through DNA‐based self‐assembly shell‐satellite nanostructures. It is reported that the chiral nanoassemblies are enantiomer‐dependent and structure‐induced photosensitizers under circular polarized light (CPL) irradiation. The developed structures have an extremely high phototherapeutic effect for cancer cells, well dispersed throughout the cell, and show no cytotoxicity.